β-Cell Replacement Strategies: The Increasing Need for a “β-Cell Dogma” - Vieira, Andhira; Druelle, Noémie; Avolio, Fabio; Napolitano, Tiziana; Navarro-Sanz, Sergi; Silvano, Serena; Collombat, Patrick (Frontiers in Genetics, 2017)
Type 1 diabetes is an auto-immune disease resulting in the loss of pancreatic β-cells and, consequently, in chronic hyperglycemia. Insulin supplementation allows diabetic patients to control their glycaemia quite efficiently, but treated patients still display an overall shortened life expectancy and an altered quality of life as compared to their healthy counterparts. In this context and due to the ever increasing number of diabetics, establishing alternative therapies has become a crucial research goal. Most current efforts therefore aim at generating fully functional insulin-secreting -like cells using multiple approaches. In this review, we screened the literature published since 2011 and inventoried the selected markers used to characterize insulin-secreting cells generated by in vitro differentiation of stem/precursor cells or by means of in vivo transdifferentiation. By listing these features, we noted very important discrepancies comparing the different approaches for the initial characterization of insulin-producing cells as true β-cells. Considering the recent advances achieved in this field of research, the necessity to establish strict guidelines has become a subject of crucial importance, especially should one contemplate the next step, that is the transplantation of in vitro or ex vivo generated insulin-secreting cells in type 1 diabetic patients.